Perceived School Characteristics Fostering Civic Engagement Among Adolescents in Italy - Tzankova, Iana I.; Albanesi, Cinzia; Cicognani, Elvira (Frontiers in Political Science, 2021)
It has been widely argued that effective citizenship education should focus on more than mere teaching of civic knowledge, but should provide a wider range of opportunities for the experience of participation and development of skills, efficacy and interest instrumental to active citizenship. Opportunities for critical reflection such as open classroom discussions, fairness at school, institutional efficacy and student participation at school activities have been linked to the development of civic and political attitudes. The capacity of school education to provide opportunities for critical reflection on students’ participative experiences, however, has not been explored empirically sufficiently. This paper aims to identify the contribution of different school characteristics to the development of civic and political attitudes and their impact on students’ level of participation in civic activities through a mixed methods study. Questionnaire data collected in two waves with 685 adolescents from Italy were analyzed through structural equation modeling to test the effects of school characteristics at Time 1 (democratic climate, student participation and critical reflection) on civic participation at Time 2, mediated by institutional trust, civic efficacy and political interest. In order to explore the quantitative findings and examine further students’ perceptions of the school aspects that support their civic involvement, focus group discussions were conducted with students from secondary schools with different tracks.The results highlight the importance of opportunities for active involvement in school and critical reflection in fostering political interest, efficacy and civic participation. Democratic school climate was found to impact institutional trust and civic efficacy, but not participation. Students’ accounts of schools’ citizenship education activities highlight further the need for a participative environment that rises above information transmission by inviting critical reflection and giving value to students’ active involvement in the institution.